Prevalence and Antimicrobial Resistance Pattern with Associated Gens of Extended Spectrum β- lactamase, Carbapenemases and Methicillin Resistant Staphylococcus aureus Producing Organisms isolated from Neonatal Sepsis in Dhaka City of Bangladesh - Rahman, Md. Anisur; Uddin, Bhuiyan Mohammad Mahtab; Ratan, Zubair Ahmed; Salman, Mohammad Nahid; Yeasmin, Mst. Marufa; Mahjabin, Mosfika (Bangladesh Journal of Medical Microbiology, 2025)
Background: Extended spectrum β-lactamase (ESBL), carbapenemases and MRSA producing organisms led to serious concern about septicaemic neonates in neonatal intensive care units (NICU) due to high resistance against commonly used antimicrobial agents. Objective: The purpose of the present study was to assess the prevalence and resistance pattern of ESBL, carbapenemases (MBL) and MRSA producing organisms isolated from cases of neonatal septicaemia at a tertiary care hospital Dhaka, Bangladesh. Methodology: This cross-sectional study was conducted in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh and samples were collected from the NICU of Department of Paediatrics at Dhaka Medical College Hospital, Bangladesh, from the period of July 2015 to June 2016, included neonates with suspected septicemia. Susceptibility testing was done by disc diffusion and MIC methods. All Isolates were screened for ESBL, MBL and MRSA production by phenotypic methods and genes encoding mecA, PVL among the MRSA strains, blaCTX-M-15, blaOXA-1 among phenotypically confirmed ESBLs producers and class A (KPC), class B (NDM-1, VIM, IMP), class D (OXA-48, OXA-181) carbapenemases among meropenem resistant isolates were detected by PCR. Results: Out of 200 neonates, 106(53%) were culture positive among them 18 (31.03%) were ESBL producers. Rate of resistance was highest for ampicillin, cephalosporins and aminoglycosides. Twelve (66.67%) ESBL producers were positive for blaCTX-M-15 and 6 (33.33%) were positive for blaOXA-1 with consensus primers. Twenty-two (56.41%) carbapenemases encoding genes were detected and all were resistant to 3rd generation cephalosporins, amoxicillin/ clavulanic acid, gentamicin, cefoxitin, carbapenems and netilmycin. Fifteen (62.50%) MRSA were detected and all were mecA gene positive, 4 (26.67%) were positive for PVL gene, all MRSA were sensitive to vancomycin and linezolid. Conclusion: In conclusion it has found that ESBL, carbapenemase and MRSA producers in NICU are resistant to classical empirical therapy. Bangladesh Journal of Medical Microbiology, July 2024;18(2):114-119